Correlative microscopy of freeze-dried cells and studies on intracellular calcium stores with imaging secondary ion mass spectrometry (SIMS). Issue 10 (6th September 2019) - Chandra, Subhash
Abstract : Secondary ion mass spectrometry (SIMS)-based imaging techniques have become effective tools for studies of elements and molecules in biological samples. Abstract : Secondary ion mass spectrometry (SIMS)-based imaging techniques have become effective tools for studies of elements and molecules in biological samples. In the current work, a correlative microscopy approach was applied to cryogenically prepared fractured freeze-dried cells for organelle-level imaging of chemical composition using SIMS. A CAMECA IMS-3f SIMS ion microscope was used for studying the effect of microtubule-perturbing agents, specifically nocodazole and taxol, on intracellular calcium stores. The perturbation of microtubules in renal epithelial LLC-PK1 cells resulted in significant loss of total calcium in both the nucleus and cytoplasm. In another study, the stable isotope 44 Ca was used for imaging the influx of calcium in resting and stimulated LLC-PK1 cells. SIMS imaging of two calcium isotopes, 44 Ca and 40 Ca, in the same cell revealed the distribution of calcium influx in the 44 Ca image and endogenous calcium in the 40 Ca image. An arginine-vasopressin treatment of cells showed that the Golgi apparatus is sensitive to hormonal stimulation.